(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2026)
Background: Intussusception is an important cause of intestinal obstruction in children. The diagnosis is primarily based on clinical findings; however, no universal diagnostic signs or symptoms are present in every patient. Preventing complications and fatalities caused by delayed diagnosis and surgery requires prompt medical attention. In this study, the accuracy of ultrasonography was investigated using per-operative findings as a gold standard. Objective: To assess the accuracy of ultrasonography in detecting intussusception in children using per-operative findings as the gold standard. Materials and Methods: This cross-sectional study was conducted from January 2022 to December 2023 at Sir Salimullah Medical College & Mitford Hospital in Dhaka, Bangladesh. A total of 42 patients were included in the study according to predefined inclusion and exclusion criteria. Statistical analysis was done by SPSS version 27. Results: Among the study participants, 66.66% children were under 1 year of age with male predominance (69%). Ultrasonography accurately diagnosed intussusception in 37 cases (88.09%). The sensitivity, specificity, PPV, NPV, and accuracy of ultrasonography for the diagnosis of intussusception were 97.29%, 80 %, 97.29%, 80% and 95.23% respectively. Conclusion: According to the study, ultrasonography has a satisfactory level of sensitivity, specificity, and accuracy to diagnose intussusception. Most crucially, ultrasonography can identify this condition with assessment of vascularity. Therefore, ultrasonography can be considered a reliable first-line imaging modality for diagnosing intussusception in children, as it avoids exposure to ionizing radiation from CT scans and X-rays. Journal of Paediatric Surgeons of Bangladesh (2025) Vol. 16 (1 & 2): 8-14